In Vivo Attenuation of Antibody-Mediated Acute Renal Allograft Rejection by Ex Vivo TGF-β-Induced CD4(+)Foxp3(+) Regulatory T Cells - Liao, Tao (Front Immunol, 2017)
Antibody-mediated rejection (AMR) has emerged as the major cause of renal allograft dysfunction, and more effective strategies need to be explored for improving transplant outcomes. Regulatory T cells (Tregs), consisting of at least natural and induced Treg subsets, suppress effector responses at multiple levels and play a key role in transplantation tolerance. In this study, we investigated the effect of induced Tregs (iTregs) on preventing antibody-mediated renal injury and rejection in a mouse model. We observed that infusion of iTregs markedly attenuated histological graft injury and rejection and significantly improved renal allograft survival. iTregs exhibited a comprehensive ability to regulate immunological disorders in AMR. First, iTreg treatment decreased the levels of circulating antidonor antibody and the antibody deposition within allografts. Second, iTregs significantly reduced cell infiltration including CD4(+) T cells (including Th1, Th17, and Tfh), CD8(+)IFN-γ(+) cells, natural killer cells, B cells, and plasma cells, which are involved in the process of AMR. Our results also highlight a predominance of M1 macrophage infiltration in grafts with acute AMR, and M1 macrophage could be reduced by iTreg treatment. Collectively, our data demonstrate, for the first time, that TGF-β-induced Tregs can attenuate antibody-mediated acute renal allograft injury through targeting multiple effectors. Thus, use of iTregs in prevention of AMR in clinical practice could be expected.